Diversity of Fish Species in Lubuk Larangan Kampung Surau, Gunung Selasih Village, Pulau Punjung Sub-district, Dharmasraya Regency - Robianto Robianto; Hafrijal Syandri; Azrita Azrita (Pascasarjana, Universitas Negeri Padang, 2022)
This paper discusses the diversity of fish species in the Lubuk Prohibition of Kampung Surau, Nagari Gunung Selasih, Pulau Punjung Sub-district, Dharmasraya Regency. This study was conducted for one month from April 1-30, 2022. The results of the study found 16 fish species from 4 orders, 6 families, and 16 genera. Among the species collected, the most dominant is the order Cypriniformes with 68.75% followed by the order Perciformes and the order Cypriniodontiformes with 12.50% each, and the order Anabantifoemes with 6.25% of the total fish species. Species with vulnerable status are Hemibagrus mumurus, Barbonymus gonionotus, Cyclocheillichthys Apogon, Macrochirichthys macrochirus, and Osphronemus goramy.